1998
DOI: 10.1063/1.122312
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier engineering in III–V nitrides via the piezoelectric effect

Abstract: A method for enhancing effective Schottky barrier heights in III-V nitride heterostructures based on the piezoelectric effect is proposed, demonstrated, and analyzed. Two-layer GaN/Al x Ga 1Ϫx N barriers within heterostructure field-effect transistor epitaxial layer structures are shown to possess significantly larger effective barrier heights than those for Al x Ga 1Ϫx N, and the influence of composition, doping, and layer thicknesses is assessed. A GaN/Al 0.25 Ga 0.75 N barrier structure optimized for hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(63 citation statements)
references
References 10 publications
5
58
0
Order By: Relevance
“…This will increase the resulting SBH at the metal/8H (partial) interface, as illustrated in Figure 3(b). This proposal is analogous to that proposed by Yu et al 16 for a GaN/Al x Ga 1Àx N/GaN/metal structure. To test this assertion, we chemi-mechanically polished another piece of sample cut from the same wafer to remove the surface groove structure (along with any surface-exposed 8H tail), used BEEM to locate the (polished) inclusion opening (visible as a line of low SBH), and then measured the SBH as a function of distance away from the opening.…”
supporting
confidence: 54%
“…This will increase the resulting SBH at the metal/8H (partial) interface, as illustrated in Figure 3(b). This proposal is analogous to that proposed by Yu et al 16 for a GaN/Al x Ga 1Àx N/GaN/metal structure. To test this assertion, we chemi-mechanically polished another piece of sample cut from the same wafer to remove the surface groove structure (along with any surface-exposed 8H tail), used BEEM to locate the (polished) inclusion opening (visible as a line of low SBH), and then measured the SBH as a function of distance away from the opening.…”
supporting
confidence: 54%
“…[52] In addition, Yu et al increased the barrier heights of Ni in AlGaN/GaN heterostructure by 0.37 eV using the piezoelectric effect. [53] In this study, we observed high barrier heights over 1 eV for the Ti/Al or Pd/Al contacts on N-face n-GaN substrate. Therefore, the opposite electrical properties of the Ti/Al contacts depending on crystal polarity was observed in this study, which can be explained the opposite piezoelectric field in AlN/GaN heterostructure relying on crystal polarity of the free-standing n-GaN substrate.…”
Section: Carrier Transport In Metal Contacts To N-face N-gan Of Alingmentioning
confidence: 80%
“…This scheme is referred to as the "advancing metallization" here. In the conventional scheme, 710 Å of Al reacts with 250 Å of Ti to form Al 3 …”
Section: Approaches To Fabricate Low Resistance-contact In a Morementioning
confidence: 99%
“…Internal photo emission is an alternative way to determine the Schottky barrier height of a metal/AlGaN/GaN heterostructure. In our laboratory, we have measured the barrier height of Ni of Al 0.15 Ga 0.85 N (300 Å and 500 Å)/GaN using the internal photo emission technique and obtained a barrier height of ~1.30 eV, independent of the AlGaN layer thickness [3] . This value, well within the experimental scattering range, is considered to be consistent with the value obtained on bulk Al 0.15 Ga 0.85 N samples.…”
mentioning
confidence: 99%